Building integrated renewable energy. Issue 2 (March 2021) - Lin, Yaolin; Yang, Wei; Hao, Xiaoli; Yu, Changxiong
About one-third of the primary energy in the world is consumed by buildings. A large amount of CO2 emission due to building energy consumption has threatened the sustainable development of the world. Improvement on the building energy performance, especially by integration with renewable energy resources has attracted interest worldwide to reduce greenhouse gas emission to make our society more sustainable. This Special Issue on building integrated renewable energy was open to all contributors in the field of building energy efficiency. The original experimental studies, numerical simulations, and reviews in all aspects of renewable energy utilization, management, and optimization have been considered. In the event, all these topics were covered in the extensive submissions accepted, but interesting papers on other aspects of building energy efficiency were also received. The purpose of this editorial is to summarize the main research findings of accepted papers in this Special Issue, including the use of renewable energy and energy saving technologies in buildings and identify a number of research questions and research directions.